PEDAGOGICAL - ACADEMIC EXTENSION ON DIAGNOSIS AND FIGHT AGAINST CERVICAL CANCER: AN EXPERIENCE REPORT - de Araújo Holanda Soares, Josué; Fernandes de Menezes Brito, Bárbara; Almeida Rosal Oliveira, Júlia; Martins Silva, Lorenna; Gabriele Batista Vilela, Nádilah; Sthéfane Quaresma de Sousa, Thaís (Brazilian Medical Students, 2021)
INTRODUCTION: Cervical Cancer (CC) is one of the most common malignancies among women worldwide. In Brazil, it is the third most incident and the fourth cause of cancer mortality in women, without considering non-melanoma skin tumors1. This disease settles in the uterine cervix and its main risk factor is the infection by Human Papilloma Virus (HPV) with carcinogenic potential, mainly types 16 and 18, responsible for about 70% of cervical cancers. With this work, it is intended to report experience of academic-pedagogical action, carried out to instruct students on how to prevent and diagnose CC. REPORT: The activity “Cancer of the Cervix, not here!”, organized by the student department, took place during the “Março Lilás” period, via virtual platform and was taught by a gynecologist. 89 students participated. The initial approach was a recorded reenactment of a problem situation. Afterwards, the lecture started and was explained about HPV, the levels of prevention, diagnosis and the importance of CC. At the end of the action, participants were encouraged to reflect, with a moment of exposure and resolution of the issues raised. DISCUSSION: It reflected on the person-centered consultation, vaccination and Pap smear. This activity provided experimentation with dynamic ways of teaching students, who were hampered by the suspension of classes and face- to-face services due to the quarantine. It also highlighted the decrease in performance of CC screening during the COVID-19 pandemic. The lecture also served as an incentive for future studies on the impact of the pandemic on CC screening. CONCLUSION: The discussions held by the invited professional allowed the understanding, by the students, of ways to prevent CC, the possible clinical manifestations of HPV in females, the importance of self-care and screening, in addition to diagnosis and treatment.